Malignant lymphoma presenting as bilateral sensorineural hearing loss—A case report. Issue 12 (13th December 2022) - Raunio, Frida; Kelppe, Jetta; Hafrén, Lena
Abstract: Bilateral Sensorineural Hearing Loss is a rare disease that is often associated with other complex medical conditions. Primary central nervous system lymphoma is an uncommon and aggressive variant of non‐Hodgkin lymphoma that can mimic many other neurological diseases. Herein, we present a rare case of lymphoma of the CNS as the etiology for progressive SSNHL. We describe a 58‐year‐old male with previous IgG4‐disease presentation who was diagnosed with progressive sensorineural hearing loss. The condition evolved rapidly despite proper, conventional therapy. The patient acquired vestibular symptoms and other cranial nerve deficiencies and he was diagnosed with intracranial lymphoma, mainly in the cerebellar region. This case demonstrates that rare intracranial lymphoma can present initially as sensorineural hearing loss. A higher suspicion for malignancy should be held in mind for patients with a history of IgG4‐related diseases and for patients presenting with progressing bilateral SSNHL that is not responding to therapy. Abstract : A suspicion for malignancy should be held in mind for patients presenting with progressing bilateral SSNHL that is not responding to therapy.